Analisis Faktor Yang Berhubungan Dengan Kinerja Perawat Dalam Pengisian Rekam Medis Elektronik Di Ruang Rawat Inap Rs Bhayangkara TK. II Hoegeng Imam Santoso Banjarmasin - Titis Nastiti; Triawanti Triawanti; Herawati Herawati; Adi Nugroho; Eko Suhartono (Universitas Islam Kalimantan Muhammad Arsyad Al Banjari Banjarmasin, 2025)
Medical records are essential to health services. In Indonesian hospitals, RME is utilized to a degree of 65%. The Bhayangkara TK III Hoegeng Imam Santoso Hospital in Banjarmasin has RME filling completeness rates that range from 42% in the inpatient room to less than 60% between August and December. evaluating how well nurses performed in filling out electronic medical records in the inpatient room of Bhayangkara Hospital TK III Hoegeng Imam Santoso Banjarmasin by looking at knowledge, tenure, work motivation, and job design. This study used a cross sectional design. The research subjects consisted of 42 nurses in the inpatient room of Bhayangkara TK III Hoegeng Imam Santoso Hospital Banjarmasin Data analysis of chi square test and multiple logistic regression test. The results of the analysis with chi square showed the p value of knowledge (p = 0.000), tenure (p = 0.4390, work motivation (p = 0.032), and job design (p = 0.004). Knowledge variable is most associated with nurse performance (Exp(B)= 14.993. There is a relationship between knowledge, work motivation, and job design. There was no relationship between length of service and nurses' performance in filling out electronic medical records in the inpatient room of Bhayangkara Hospital TK III Hoegeng Imam Santoso Banjarmasin. The most dominant variable is knowledge